A multivariate analysis of health risk assessment, phytoremediation potential, and biochemical attributes of Spinacia oleracea exposed to cadmium in the presence of organic amendments under hydroponic conditions. Issue 5 (16th April 2019) - Shamshad, Saliha; Shahid, Muhammad; Dumat, Camille; Rafiq, Marina; Khalid, Sana; Sabir, Muhammad; Missen, Malik M. S.; S. Shah, Noor; Farooq, Abu Bakr Umer; Murtaza, Behzad; Niazi, Nabeel Khan
Abstract: Cadmium (Cd) phytoremediation potential and its accumulation in edible and nonedible plant tissues is the function of various biochemical processes taking place inside plants. This study assessed the impact of organic ligands on Cd phyto uptake and different biophysiochemical processes of Spinacia oleracea L., and associated health hazards. Plants were exposed to Cd alone and chelated with citric acid (CA) and ethylenediaminetetraacetic acid (EDTA). Results revealed that the effect of Cd on lipid peroxidation, H2 O2 production and pigment contents varied greatly with its applied level and the type of organic ligand. Moreover, the effect was more prominent in root tissues than leaf tissues and for high concentrations of Cd and organic ligands. Cadmium accumulation increased by 90 and 74% in roots and leaves, respectively, with increasing Cd levels (25–100 µM). Cadmium exposure at high levels caused lipid peroxidation in roots only. Application of both CA and EDTA slightly diminished Cd toxicity with respect to pigment contents, lipid peroxidation and hydrogen peroxide (H2 O2 ) contents. Hazard quotient (HQ) of Cd was <1.00 for all the treatments. Under nonlinear effect of treatments, multivariate analysis can be an effective tool to trace overall effects/trends.